Static stretch training versus foam rolling training effects on range of motion: a systematic review and meta-analysis - Konrad, A.; Alizadeh, S.; Hadjizadeh Anvar, S.; Fischer, J.; Manieu, J.; Behm, D. G. (Sports Medicine, 2024)
Background: Long-term static stretching as well as foam rolling training can increase a joint`s range of motion (ROM). However, to date, it is not clear which method is the most effective for increasing ROM. Objective: The purpose of this systematic review and meta-analysis was to compare the effects of static stretching and foam rolling training on ROM. Methods: The literature search was performed in PubMed, Scopus, and Web of Science to find the eligible studies. Eighty-five studies (72 on static stretching; and 13 on foam rolling) were found to be eligible with 204 effect sizes (ESs). For the main analyses, a random-effect meta-analysis was applied. To assess the difference between static stretching and foam rolling, subgroup analyses with a mixed-effect model were applied. Moderating variables were sex, total intervention duration, and weeks of intervention. Results: Static stretch (ES = - 1.006; p < 0.001), as well as foam rolling training (ES = - 0.729; p = 0.001), can increase joint ROM with a moderate magnitude compared with a control condition. However, we did not detect a significant difference between the two conditions in the subgroup analysis (p = 0.228). When the intervention duration was = 4 weeks, however, a significant change in ROM was shown following static stretching (ES = - 1.436; p < 0.001), but not following foam rolling (ES = - 0.229; p = 0.248). Thus, a subgroup analysis indicated a significant favorable effect with static stretching for increasing ROM compared with foam rolling (p < 0.001) over a shorter term (= 4 weeks). Other moderator analyses showed no significant difference between static stretch and foam rolling training on ROM. Conclusions: According to the results, both static stretching and foam rolling training can be similarly recommended to increase joint ROM, unless the training is scheduled for = 4 weeks, in which case static stretching demonstrates a significant advantage. More studies are needed with a high-volume foam rolling training approach as well as foam rolling training in exclusively female participants.